Health and Psychological Determinants of Uncontested Divorce in the City of Kermanshah - Amirali Babaei; Mostafa Amini-Rarani; Mahmoud Keyvanara (Shahid Beheshti University of Medical Sciences, 2020)
Background: Because of the increasing trend of uncontested divorce in the courts, as two out of every three divorces are related to uncontested divorce, scrutinizing the health and psychological causes of the rate of uncontested divorce is of great importance. The aim of this study was to examine the psychological and health factors affecting uncontested divorce Methods: The present study was a cross-sectional data secondary analysis in which the existing data were analyzed. After obtaining official permission from the family courts in the city of Kermanshah, the data related to the issue of uncontested divorce during 2017 and 2019 were received and analyzed. The sampling method in this study was a census in which all legal cases of applicants for uncontested divorce in city of Kermanshah in the years of 2017-2018 have been reviewed. Results: 2842 cases referred to welfare organization for consultation, of which, 2331 cases led to uncontested divorce and 511 cases not led to uncontested divorce (compromise). Among the psychological factors, the variables of suspicion, pessimism and depression; and among health variables, the variable of sexual satisfaction had a statistically significant relationship with uncontested divorce and anxiety, aggression and infertility did not have a statistically significant relationship. Conclusion: Considering the role of suspicion and pessimism, depression and sexual dissatisfaction in uncontested divorce, it was recommended that specific preventive strategies should be considered by the authorities. These strategies can provide both education and counseling in pre-marital and post-marital periods, as well as during the uncontested divorce process.